2009
DOI: 10.1097/ftd.0b013e3181a8cc0a
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Glucuronidation Activity of Drugs in Neonates: Extensive Interindividual Variability Despite Their Young Age

Abstract: Compared with phase I isoenzymes, data on isoenzyme-specific phenotypic activity of uridine diphosphate glucuronosyltransferase (UGT) and its covariates in neonates are limited. In vivo observations on morphine, paracetamol (acetaminophen), and propofol disposition throughout childhood confirm the overall low-glucuronidation activity in neonates observed in in vitro studies. In addition to the phenotypic low-glucuronidation activity, in vivo observations of bilirubin (UGT1A1), morphine (UGT2B7), paracetamol (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 40 publications
(96 reference statements)
0
47
0
1
Order By: Relevance
“…Activity remains low in the first 10 days of post-natal life and then begins to increase in both term and preterm babies [50]. Again co-morbidities, surgery and gene polymorphisms can affect this pattern of development [45]. The capacity of morphine metabolism by UGT2B7 is closely related to body weight as opposed to surface area and post-natal age after the first 10 days of life.…”
Section: Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Activity remains low in the first 10 days of post-natal life and then begins to increase in both term and preterm babies [50]. Again co-morbidities, surgery and gene polymorphisms can affect this pattern of development [45]. The capacity of morphine metabolism by UGT2B7 is closely related to body weight as opposed to surface area and post-natal age after the first 10 days of life.…”
Section: Metabolismmentioning
confidence: 99%
“…Factors affecting the development of this pathway include post-natal and post-menstrual age, other medications, genetic polymorphisms, co-morbidities and maternal smoking status [45]. Phenobarbitone administration has been reported to induce UGT1A1 activity [49].…”
Section: Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, Strassburg et al demonstrated that children had lower hepatic glucuronidation activities than adults [23]. In vivo, low glucuronidation activities in children were characterized for morphine (UGT2B7), paracetamol (UGT1A6) and propofol (UGT1A9) [27]. The identification of the responsible UGT isoforms and genotype-phenotype studies should be evaluated in further research.…”
Section: Figurementioning
confidence: 99%
“…In the case of lack of change in the acetaminophen/acetaminophen glucuronide phenotyping index, the investigator will have relevant information on the UGT1A pool, as previously studied using acetaminophen as a probe (Volak et al 2013). In the case that there is a change, additional investigations could be performed using more specific probes such as endogenous bilirubin (UGT1A1) or propofol (UGT1A9) as already reported in neonates (Allegaert et al 2009). …”
Section: Discussionmentioning
confidence: 97%